World watch geography skills Book 3 A geography skills book for grade 8 - Reilly, Carmel; Brasch, Nicholas (Karachi: Oxford university press, 2024)
Developed along the guidelines of national curriculum of Pakistan 2022. It is an extension of World watch social studies to the lower secondary level. It$1 (Bs aim to foster students$1 (Bgeographical literacy, spatial awareness, critical thinking and practical application of geographical concepts to enhance their overall understanding of the world and their place within it.s
Keywords: Oxford - geography skillsbook